2017
DOI: 10.1149/2.0311704jss
|View full text |Cite
|
Sign up to set email alerts
|

Communication—Corrosion Behavior of Tungsten Metal Gate in the Presence of Hydrogen Peroxide at Acidic Medium

Abstract: Herein, the corrosion behaviors of W metal gates in the presence of H 2 O 2 at the acidic medium were investigated as a function of dipping time, temperature, and H 2 O 2 concentration. We determined the kinetic constants (i.e. k w and k h ) based on the experimental data. The activation energy (E a ) are calculated from the Arrhenius equation. Thermodynamic parameters ( G ‡ , H ‡ , and S ‡ ) for the dissolution were determined based on the Eyring plot. These results investigated in this study will provide res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In the absence of Fe 3+ ions, the slurry corrosion potential was lowest, indicating a limited oxidation capability. Meanwhile, the corrosion current was highest because W dissolved in H 2 O 2 , 19,20 which is consistent with the low COF during the W CMP process (Fig. 2b).…”
Section: Resultssupporting
confidence: 72%
“…In the absence of Fe 3+ ions, the slurry corrosion potential was lowest, indicating a limited oxidation capability. Meanwhile, the corrosion current was highest because W dissolved in H 2 O 2 , 19,20 which is consistent with the low COF during the W CMP process (Fig. 2b).…”
Section: Resultssupporting
confidence: 72%
“…This unique dissolution phenomenon is another major reason for choosing tungsten wires. The dissolution of tungsten in H 2 O 2 can be expressed by the following reaction Formulas (1)–(3) [ 44 ]: W(s) + 2H 2 O 2 → WO 2 (s) + 2H 2 O, 2WO 2 (s) + 6H 2 O 2 → H 2 W 2 O 11 (aq) + 5H 2 O, 3H 2 W 2 O 11 (aq) + 7H 2 O → 2H 2 W 3 O 12 (aq) + 8H 2 O 2 , …”
Section: Methodsmentioning
confidence: 99%
“…Also, in some cases, chemical reactions like the Fenton reaction are spontaneous exothermic processes, contribute to temperature increase during polishing. (ii) Case II: As is well known, with increasing temperature of the system, the rates of chemical reactions increase [118], leading to higher removal rates [116,119,120]. Kim et al reported that the slurries at higher temperatures lead to the formation of the soft layers on the surface of SiO 2 film, and this layer could be easily removed by mechanical abrasion [116,119].…”
Section: The Effect Of Temperature Changes On the Chemical And Mechanical Reactions During Polishingmentioning
confidence: 99%